2011
DOI: 10.3109/0284186x.2011.614636
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for the EORTC QLQ-C30 quality of life questionnaire in a random sample of the Swedish population

Abstract: The reference values provided can be used as a surrogate baseline measure in HRQL research, and when evaluating the effect of interventions on HRQL in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
116
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 15 publications
21
116
8
1
Order By: Relevance
“…Based on the QLQ-C30 functional scale, the mean scores for self-reported cognitive (84), emotional (80), and social functioning (87) were lower than reported for role (91) and physical functioning (92). These values are similar to the mean scores reported for a reference population of healthy adults [16] (Table 2). Self-reported symptoms of fatigue, pain and insomnia were the highest mean scores reported on the QLQ-C30 symptom subscale or item.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Based on the QLQ-C30 functional scale, the mean scores for self-reported cognitive (84), emotional (80), and social functioning (87) were lower than reported for role (91) and physical functioning (92). These values are similar to the mean scores reported for a reference population of healthy adults [16] (Table 2). Self-reported symptoms of fatigue, pain and insomnia were the highest mean scores reported on the QLQ-C30 symptom subscale or item.…”
Section: Resultssupporting
confidence: 88%
“…Comparison of the study results to a reference population of independently functioning healthy adults, showed no significant difference in baseline QOL scores in QLQ-C30 domains except for increased financial burdens [16], which is likely due to expenses related to cancer care. Reports assessing QOL in pediatric patients have demonstrated lower overall QOL in children with CNS tumors compared to their healthy counterparts [9, 18]; however, those patients were either undergoing or within one year of treatment completion, while the majority of the participants in this study were several years post treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The values were then in the range of a normal age-standardized Swedish female population. 19 Increased frequency of diarrhea and other intestinal problems as well as urinary frequency were the only exceptions and were recorded as significant remaining adverse effects at 12 months after the external pelvic radiotherapy. No significant adverse effects different from the normal population were noted in the group receiving vaginal brachytherapy alone.…”
Section: Discussionmentioning
confidence: 97%
“…As with chronic pain, the prevalence rates of disabling pain depend on the instruments used. In the German 2012 survey of our study group [14], 7.7% of the general population met the criterion of disabling pain, as defined by the regional pain scale [28] and by a quality of life questionnaire of the European Organisation for Research and Treatment of Cancer QLQ-C30 Version 3.0 [30]. In the Canadian surveys the percentages of persons with disabling pain defined by any limitation of activities by pain or discomfort ranged from 11.4% to 13.3% [27].…”
Section: Discussionmentioning
confidence: 99%